PENGARUH UKURAN PERUSAHAAN, COLLATERALIZABLE ASSETS DAN LEVERAGE TERHADAP DIVIDEND PAYOUT RATIO DENGAN PROFITABILITAS SEBAGAI PEMODERASI - Navia Andica; Syahril Djaddang; Suyanto Suyanto (Universitas Trilogi, 2022)
The dividend policy is applied by the company in determining the profits to be distributed to shareholders and has been approved for dividend payments. This study aims to analyze company size, collateralizable assets, leverage, profitability and dividend payout ratio in listed manufacture companies simultaneously (IDX) for the 2015-2020 period. This study is to analyze the partial effect of firm size, collateralizable assets and leverage on and dividend payout ratio with profitability as a moderating variable. The analytical method used is descriptive statistical testing and moderated regression analysis (MRA). The sampling technique in this study used a sampling method based on criteria with a predetermined purpose of sampling and 32 companies were obtained as research samples. The results showed that the size of the company and collateralizable assets had no significant effect on the DPR, while leverage had significant negative effect on the DPR. Profitability as a moderating variable weakens the influence of firm size and leverage on the DPR, while profitability fails to weaken the moderating Collateralizable assets against the DPR.Keywords: Dividend policy, Firm size, Collateralizable asset Leverage, Profitability